Assessing the Role of Differential Herbivore Performance Among Plant Species in Associational Effects Involving the Invasive Stink Bug Bagrada hilaris (Hemiptera: Pentatomidae). Issue 1 (19th December 2018) - Lillian, Sarah; Redak, Richard A; Daugherty, Matthew P
Abstract: Co-occurring plant species can influence the extent of damage to each other by altering the activity or abundance of a shared herbivore. One mechanism by which neighboring host plants exacerbate damage to a focal host is if the neighbor amplifies herbivore populations. We studied the performance of a shared herbivore on a native and an invasive plant, to estimate how strongly the presence of the invasive plant increases local herbivore abundance—in a system in which highly asymmetric spillover herbivory may occur. Specifically, we conducted a series of greenhouse experiments that measured reproduction, development, and survival of the invasive stink bug Bagrada hilaris Burmeister on an invasive annual forb, Sahara mustard ( Brassica tournefortii ), or a native perennial shrub, four-winged saltbush ( Atriplex canescens ). All measured aspects of stink bug performance revealed consistently greater performance on Br. tournefortii . Indeed, A. canescens appears to be insufficient for Ba. hilaris to complete its development. Nonetheless, preliminary damage assessments found that both plant species were used as feeding hosts, putative feeding lesions were a more reliable indicator of herbivory than was the degree of yellowing, and higher Ba. hilaris abundance was generally associated with greater sublethal damage to A. canescens . Thus, A. canescens appears to be susceptible to Ba. hilaris herbivory, though more research is needed to assess fitness impacts of this novel herbivore. Our results indicate that differential herbivore performance among host plants may be an important contributor to observed patterns of abundance of a shared herbivore and spillover herbivory between plants.